Desaceleración intraparto por nudo verdadero ajustado de cordón umbilical - Chung Delgado, Kocfa (2014)
A true knot of the umbilical cord is a rare pathology that can put at risk the fetal wellbeing during the pregnancy and the delivery. It can be an unsuspected and sudden cause of acute fetal distrés. A pre-partum diagnosis of a true knot of the umbilical cord is complicated due to the lack of characteristic signs pregnancy. An adecuate monitoring of the fetus during the pregnancy and delivery is emphasized, especially if a vaginal delivery is decided.